2007
DOI: 10.2320/matertrans.48.385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on Phase Constitution, Lattice Parameter and Mechanical Properties of Ti-4 mol%Au Near-Eutectoid Alloy

Abstract: Effects of aging on phase constitution, lattice parameters and mechanical properties of Ti-4 mol%Au near-eutectoid alloy were investigated. The alloy was fabricated by Ar arc-melting method, followed by homogenization at 1273 K for 3.6 ks. The ingot was cold-rolled with 95% reduction in thickness, solution treated at 1173 K for 0.9 ks and quenched into ice water. It was found that the apparent phase after the solution treatment was a supersaturated solid solution of (hcp) phase. This supersaturated -phase is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…39 In the present study, the growth temperature (675-750 1C) for the nanowires is lower than the lowest eutectic temperature in the bulk Au-Ti binary system (832 1C). 40 It should be noted that the actual eutectic temperature of a nanoscale material is expected to be lower than that of the bulk under the same pressure conditions. 41 We therefore expect that the growth of these nanowires occurs by both vapour-solid and VLS mechanisms as the catalyst state changes from a solid state to a liquid state throughout the temperature range.…”
Section: Papermentioning
confidence: 99%
“…39 In the present study, the growth temperature (675-750 1C) for the nanowires is lower than the lowest eutectic temperature in the bulk Au-Ti binary system (832 1C). 40 It should be noted that the actual eutectic temperature of a nanoscale material is expected to be lower than that of the bulk under the same pressure conditions. 41 We therefore expect that the growth of these nanowires occurs by both vapour-solid and VLS mechanisms as the catalyst state changes from a solid state to a liquid state throughout the temperature range.…”
Section: Papermentioning
confidence: 99%
“…Matsuki et al found that the rapid-quenched Ti-4Au alloy performed high stability in terms of thermal property, where the performances, such as mechanical properties, were barely affected when the alloys were subject to various annealing-treatments. 22) Moreover, it was further found that after various annealing-treatments were conducted on the Ti-4Au alloys, the aforementioned undesired Ti 3 Au (crystal structure of A15) was not generated through the eutectoid phase transformation of β → α + A15. Both the abovementioned high thermal stability and phase constituent free from Ti 3 Au compound indicate that the Ti-4Au alloy could be a promising material for the practical uses.…”
Section: Determination Of the Binary Ti-au Alloymentioning
confidence: 99%
“…Besides to the thermal stability and phase constituent issues, the workability of the materials, which is also a crucial prerequisite for practical uses, is also necessary to be considered. It was discovered that, opposite to the Zr-4Au alloys possessing poor workability, the Ti-4Au alloys performed excellent workability, 22,23) which is beneficial for the synthesis of the biomedical materials with certain dimensions and shapes.…”
Section: Determination Of the Binary Ti-au Alloymentioning
confidence: 99%
See 2 more Smart Citations